Strategy Model For Internalizing The Values Of Faith And Piety Through Learning Non-Religious Courses In Islamic Higher EducationR OF ISLAMIC EDUCATION STUDENTS - Ahmad Khomaini Syafeie; Syihabuddin Syihabuddin; Kama Abdul Hakam; Aceng Kosasih; Encep Syarief Nurdin (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2026)
This study aims to develop an effective strategy model for internalizing the values of faith and piety within non-religious courses in Islamic higher education. Despite institutional expectations to cultivate holistic student character, existing instructional practices often lack structured frameworks that integrate spiritual values into general course content. Employing a Research and Development design using the ADDIE model Analysis, Design, Development, Implementation, and Evaluation this study identifies learner needs, designs value-integrated instructional components, develops prototype materials, and evaluates their feasibility and effectiveness. Mixed data from surveys, interviews, observations, expert validation, and pilot implementation reveal that the model enhances students’ spiritual awareness, engagement, and character formation without compromising academic competencies. The study concludes that the IMTAQ-based strategy model provides a practical and pedagogically grounded approach for strengthening the integration of faith and piety across non-religious course settings in Islamic higher education. Keywords: Faith and piety internalization; IMTAQ-Strategy model; Islamic higher education.